Acre prisons: remission of penalty for reading as a perspective for a desirable citizenship - Nascimento, Inez de Oliveira Lima; C. de Albuquerque Oliveira, Grassinete (The ESPecialist, 2023)
Discussions related to the deprivation of liberty deserve attention, since the humanities and language sciences occupy a prominent place by emphasizing the place of the subject at the center of society. The purpose of this text is to understand how education in prisons in Acre contributes to a desirable citizenship perspective. As a theoretical foundation, we use Foucault (1979, 1987), Zilberman and Lajolo (2011) with the concept of reading, and Petit (2010) and Goffman (2004) with discussions about education and reading in crisis spaces, in addition to other authors who deal with these themes. As it is a bibliographical study, we are based on news published on Acrean virtual sites, exclusively, Agazeta.net, to investigate how reading is understood in a context of deprivation of liberty. The results indicate that education and reading can contribute to the formation of the subject in the future search for a desirable citizenship.